Particles - Penny, Michael, 1952- (Hugh MacLennan poetry series., 2011)
Michael Penny addresses his poems directly to the reader, challenging you to satisfy your need to investigate and understand the sensory and intellectual assumptions we use to make sense of our world. Balanced between abstract metaphysical challenges and the concrete and commonplace, Penny's poetry considers a range of topics, including cars, bruises, lotteries, pine needles, and dogs, infusing each with strangeness and unexpected intrigue. A lively and surprising collection, Particles joins together inner and outer space and suggests that you might not know what you think you know.